A Five-Hundred-Year-Old Uncorrected Editorial Accident : The Insertion of Cajetanian Text into a Scotist’s Commentary - de Oliveira Astorga, Luiz (Laval théologique et philosophique, 2015)
In this paper I demonstrate that a large section of a Cajetanian text was accidentally copied into the work of one of his most vehement critics, Fr. Francesco Licheto, a prominent professor and commentator of Duns Scot’s thought. The text was originally inserted without markings or observations and ends the section of commentary giving the reader the exact opposite view of what the actual author had intended. The mistake seems to have evaded editors for centuries and has perpetuated itself in the five major editions that contain Licheto’s work, two of them being Scot’s Opera Omnia, those of 1639 and 1893.